2019
DOI: 10.1111/aos.14304
|View full text |Cite
|
Sign up to set email alerts
|

Ciliary muscle dimensions by swept‐source optical coherence tomography and correlation study in a large population

Abstract: Purpose: To examine ciliary muscle (CM) dimensions in vivo by swept-source optical coherence tomography (SS-OCT) in a large healthy population. To assess the reproducibility of CM measurements and correlations with different parameters. Methods: In this cross-sectional study, the following CM measurements were made in 495 eyes of 495 subjects in the temporal and nasal quadrants: length (CML), area (CMA) and thickness at distances of 1000 lm (CMT1), 2000 lm (CMT2) and 3000 lm (CMT3) from the scleral spur using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
2
20
3
Order By: Relevance
“…Other investigators, however, have not reported a difference between nasal and temporal TM values (Fernandez-Vigo et al, 2017;Chen et al, 2018). In most studies, a significantly larger CMA and thicker CM in the temporal quadrant was detected (Sheppard and Davies, 2010;Fernández-Vigo et al, 2020). In current study, the CMA (P < 0.001) was also significantly larger in the temporal quadrant.…”
Section: Discussioncontrasting
confidence: 59%
See 3 more Smart Citations
“…Other investigators, however, have not reported a difference between nasal and temporal TM values (Fernandez-Vigo et al, 2017;Chen et al, 2018). In most studies, a significantly larger CMA and thicker CM in the temporal quadrant was detected (Sheppard and Davies, 2010;Fernández-Vigo et al, 2020). In current study, the CMA (P < 0.001) was also significantly larger in the temporal quadrant.…”
Section: Discussioncontrasting
confidence: 59%
“…Similarly, Chen et al ( 2018) noted a clear decline in the SC diameter and CSA as age increased, with a linear correlation analysis indicating a significant age-dependent tendency (P < 0.001) using the CASIA SS-1000 OCT. Zhao et al (Zhao et al, 2018) divided participants into four groups (16-20 years, 21-40 years, 41-60 years, and 61-80 years) and found that the nasal CSA was significantly smaller in the 61-80-years group. Studies have also reported that the crystalline lens thickness increases, the anterior lens curvature steepens, and the IA-SS and CMA decrease with age (Richdale et al, 2013(Richdale et al, , 2016Fernández-Vigo et al, 2020;Xie et al, 2020). Previous studies have reported that the SC size increases in response to accommodation efforts and shrinks with cycloplegia in children (Daniel et al, 2018;Xiang et al, 2020).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Thickness is usually measured at a distance of 1, 2, and 3 mm (CBT1, 2 or 3 and CMT1, 2 or 3, respectively) from the scleral spur. 3340 It should be noted that the different authors refer to CB or CM measurements without distinction. Through UBM, the CB can be actually measured as it theoretically includes the CP.…”
Section: Ciliary Body Measurements Correlation and Reproducibility Studiesmentioning
confidence: 99%